Potential Risks and Their Analysis of the Apparel & Textile Industry in Turkey: A Quality-Oriented Sustainability Approach - TAÇGIN, ERTUĞRUL (INST CHEMICAL FIBRES, 2018)
The most significant issues in businesses within the scope of manufacturing and services are the sustainability of production quality, setting quality standards and reducing the waste amount during the manufacturing process. From this point of view, the aim of this study is to provide a better quality level of supplying households' apparel needs while reducing the environmental, economic and social problems of the sustainable supply chain of the apparel sector and extending the lifecycle of apparel. The importance of risk analyses and calculations in the applications of industrial sectors plays a vital role in evaluating the factors of sustainability dimensions. In order to address this risk analysis in this research, quality-oriented implementations are applied to determine the failure modes and effect analysis (FMEA). The significant factors are determined via Pareto Analysis (PA) to control and prevent potential errors and failures in the manufacturing systems of the textile industry. To achieve the aim of this study, the methodology of the research focuses on discovering failures of negative impact based on the primary factor degrees with the computing of risk priority numbers (RPNs) in the manufacturing process of the textile-apparel industry in Turkey. According to the ranking of the RPM, FMEA application and PA enable to decrease the effects of negative factors and risks as well as the waste amount of the apparel-textile industry, as well as to increase the lifecycle of apparel and products.
Keywords: failure mode; effect analysis; lifecycle; pareto analysis; quality; risk priority number; sustainability; FAILURE MODE